MEDIA PEMBELAJARAN TRAINER HUKUM OHM DAN HUKUM KIRCHOFF PADA MATA PELAJARAN DASAR LISTRIK DAN ELEKTRONIKA DI SMK NEGERI 3 SINGARAJA - Komang Perdy Trisna; I Putu Suka Arsa; Wayan Mahardika Prasetya Wiratama (Universitas Pendidikan Ganesha, 2021)
This study aims to create a learning media trainer of Ohm's Law and Kirchoff's Law which are used to assist the learning process in Basic Electrical and Electronics subjects in class X Audio Video Engineering at SMK Negeri 3 Singaraja. This research type is R & D (Research and Development). This study uses percentage statistical analysis techniques to process data from content experts, media experts, and field trials. This study used a questionnaire as an instrument for data collection for content experts, media experts, and students. The results of the research were obtained: The results of the content expert test obtained a percentage of 90.91% with very decent qualification, and the results of the media expert test obtained a percentage of 94.44% with very proper qualification. The results of the small group test with 5 respondents obtained a percentage of 100% with the lowest respondent, namely respondent 4 (R4) with a score of 49 which is classified as very good, and the results of the large group test with 25 respondents got a percentage of 100% with the lowest respondent is the respondent 9 (A9) with a score of 45 is classified as very good. Based on the result of the research, the learning media for the Ohm Law and Kirchoff Law trainers are suitable for use in the learning process in class X Audio Video Engineering at SMK Negeri 3 Singaraja in Basic Electrical and Electronics subjects.